Desenvolvimento de estruturas poliméricas bioativas macroporosas destinadas à engenharia de tecido ósseo - Soares, Gabriela Borges (2015)
Lesions in bone tissue reach 15 million cases per year worldwide. Thus, a significant amount of bone tissue transplants have been performed in recent years. A promising alternative to bone graft is in the field of tissue engineering, which is based on the use of polymeric structures acting as support for hard tissue regeneration. The objective of this project was look for the association of the PLGA copolymer, to the bioceramic hydroxyapatite, to form a polymeric bioactive macroporous structure. The preparation was made through the PLGA dissolution in chloroform, followed by addition of sodium chloride and hydroxyapatite (porogenic agent). Molding of the samples was performed by compression in hydraulic press. After, was performed the leaching of the scaffolds, followed by treatment with NaOH. Finally the composites obtained were characterized by FEG - SEM, in order to analyze qualitatively the morphology, porosity and interconnectivity of the pores; the hydrophilicity of the surface was evaluated by wettability tests it was proved chemical treatment efficiency; in vitro hydrolytic degradation assays performed as a function of time demonstrate that the percentage of degradation of various types of scaffolds did not showed significant changes between 14 and 42 days. Hydrolytic degradation assays found yet that the fluid retention was higher in scaffolds chemically treated; compression tests evaluated the mechanical behavior of different types of scaffolds made. It was concluded then that the methodology used originated macroporous composites that may be applied in bone tissue engineering.